Team collaboration using Microsoft Office for more effective teamwork - Pierce, John 1954- (Microsoft Press, 2012)
Set the stage for more effective collaboration in your organization using Microsoft Office. Whether coordinating a cross-team project or leading your workgroup, you'll discover how to combine your skills with Office programs with best practices for enabling your team's best work. Apply expert insights for increasing the collaboration power of teams and groups Take advantage of the collaboration features in Microsoft Word, Excel, PowerPoint, Outlook, and OneNote to manage shared work and communications Learn ways to use Microsoft SharePoint to enable teamwork Get an overview of capabilities and business considerations for using Microsoft Office 365.
Print version record
Keywords: Microsoft Office; Project management -- Computer programs; BUSINESS & ECONOMICS; Project Management; TECHNOLOGY & ENGINEERING; Project Management; Project management; Computer programs